Outcomes in Patients Treated with Post-mastectomy Chest Wall Radiotherapy without the Routine Use of Bolus. Issue 7 (July 2018) - Yap, M.L.; Tieu, M.; Sappiatzer, J.; Panzarella, T.; Cuartero, J.; McCready, D.; Fyles, A.
Abstract: Aims: The use of bolus in post-mastectomy radiotherapy (PMRT) varies significantly between institutions. We report on chest wall recurrence and acute toxicity rates for PMRT patients treated with selective use of bolus. Materials and methods: We analysed PMRT patients who received adjuvant chest wall radiotherapy for invasive breast cancer between 2004 and 2009. Patient, tumour and cancer outcomes were collected from a prospective database, with additional radiotherapy and acute toxicity details supplemented retrospectively. Chest wall bolus was reserved for patients considered at high risk of local recurrence. Results: There were 314 patients suitable for analysis: 52 received bolus, 262 did not. The mean age was 53.2 years. The median follow-up was 4.2 years. The most common T stage was T2 (37%), followed by T3/T4 (33%). There were 229 patients (73%) who had N+ disease; 213 (68%) patients had grade 3 cancer. Oestrogen receptor was positive in 176 (56%) cases, progesterone receptor was positive in 134 (43%) and HER2 receptor was positive in 24 (8%). Lymphovascular space invasion was present in 146 patients (46%), dermal invasion in 30 patients (10%) and positive margin in 14 patients (4%). The 4 year chest wall recurrence rate was 14% (95% confidence interval 5.4–26.8%) in the bolus group and only 3.5% (95% confidence interval 1.6–6.4%) in the non-bolus group. On univariate analysis, use of bolus was associated with a significant difference in chest wall recurrence (hazard ratio 3.09; 1.15–8.33; P  = 0.025). However, when taking into account margin status, this significance was lost (hazard ratio = 2.45; 95% confidence interval 0.80–7.50, P  = 0.12). There was a higher rate of acute grade 2 skin toxicity in patients receiving bolus compared with those without, 40% versus 21% ( P  = 0.01). Conclusions: The selective use of bolus resulted in a small risk of chest wall recurrence rates for low-risk patients. This suggests that the routine use of bolus in PMRT patients may be unnecessary. Highlights: Four year chest wall recurrence rate (CWRR) in patients not receiving bolus was 3.5%. On multivariable analysis, the use of bolus had no significant effect on CWRR. Higher grade 2 skin toxicity in patients receiving bolus compared with no bolus. The predominant site of failure in this locally advanced cohort was distant.